2009
DOI: 10.1523/jneurosci.5548-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Massage Accelerates Brain Development and the Maturation of Visual Function

Abstract: Environmental enrichment (EE) was shown recently to accelerate brain development in rodents. Increased levels of maternal care, and particularly tactile stimulation through licking and grooming, may represent a key component in the early phases of EE. We hypothesized that enriching the environment in terms of body massage may thus accelerate brain development in infants. We explored the effects of body massage in preterm infants and found that massage accelerates the maturation of electroencephalographic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
170
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(194 citation statements)
references
References 46 publications
14
170
0
10
Order By: Relevance
“…[50][51][52][53] Very recently, a protocol of daily artificial tactile stimulation has been used in the rat as a strategy to promote visual system development. 54 The authors reported that a combination of gently stroking and massaging is highly effective in accelerating the maturation of physiological visual functions, in particular of VA ( Figure 2b). Interestingly, tactile stimulation increases IGF-I levels in the visual cortex at P18, as also observed in EE animals, and blocking IGF-I action prevents the effects of massage on VA development.…”
Section: Maternal Care Tactile Stimulation and Visual System Developmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52][53] Very recently, a protocol of daily artificial tactile stimulation has been used in the rat as a strategy to promote visual system development. 54 The authors reported that a combination of gently stroking and massaging is highly effective in accelerating the maturation of physiological visual functions, in particular of VA ( Figure 2b). Interestingly, tactile stimulation increases IGF-I levels in the visual cortex at P18, as also observed in EE animals, and blocking IGF-I action prevents the effects of massage on VA development.…”
Section: Maternal Care Tactile Stimulation and Visual System Developmentioning
confidence: 99%
“…Interestingly, tactile stimulation increases IGF-I levels in the visual cortex at P18, as also observed in EE animals, and blocking IGF-I action prevents the effects of massage on VA development. 54 Tactile stimulation also compensates for inadequate maternal care: the negative effects produced by repeated episodes of maternal separation or by prenatal stress on pup growth, hormone secretion, hypothalamus-pituitary-adrenal axis and BDNF expression are all rescued by artificial massage applied to pups in order to mimic maternal behaviour. [55][56][57] Altogether, these results provide a remarkable example of cross-modal plasticity by which an increased input in a single modality reverberates as a driving force for the whole brain.…”
Section: Maternal Care Tactile Stimulation and Visual System Developmentioning
confidence: 99%
“…8,9 Enriched environments and appropriately targeted training strategies affect brain and corticospinal development and are thereby likely to influence the brain's capacity to compensate for deficits after lesions. [10][11][12] The preterm period and first year postterm might be a sensitive period for motor development; as a result, interventions during this period could be beneficial to optimize motor development. 13 A meta-analysis on effects of early interventions posthospital discharge concluded with a small significant difference in motor outcome at age 0 to 3 years favoring intervention groups.…”
mentioning
confidence: 99%
“…It reduces transepidermal water loss (TEWL) (g/m(2)/h, Mean Difference (MD) −6.80; 95% Confidence Interval (CI) −3.48, −10.15) with better skin condition and lower bacterial growth in the oil group (20% vs. 60%) and it prevents hypothermia [9]. Other positive effects include: weight gain through stimulation of the branches of the vagus nerve resulting in increased gastric activity and insulin secretion [10]; improved brain development and reduced risk of retinopathy of prematurity [11]; and conservation of heat and energy for growth [12]. Evidence from the developing world including studies from Bangladesh, Egypt, India, and Pakistan shows emollient therapy to be associated with improved weight gain and reduced risk of infection and mortality in preterm neonates [13].…”
Section: Infant Oil Massagementioning
confidence: 99%